The Implementation of Halal Tourism Ecosystem in Bantimurung as Tourism Destination - Safri Haliding; Jamaluddin Majid (STIE Amkop Makassar, 2024)
Bantimurung, as one of the most beautiful travel destinations in South Sulawesi, faces the challenge of becoming one of the halal tourism destinations in Maros South Sulawesi. The purpose of this research is to discover the halal tourism ecosystem model of Bantimurung as a tourist destination in Maros and start implementing it. This study used a descriptive method. Researchers studied the implementation of a halal tourism ecosystem model in Bantimurung National Park, Bulusaraung, Maros as a tourist destination by examining the variables of the halal tourism ecosystem. It consisted of four indicators. They are targeted products, government support, human resources, and infrastructure. Main data are interviews with Bantimurung Tourism Park Management (Local Government Tourism Board), tourism businessmen dealing with halal certification, tourism enlightenment community (Masata Maros), Indonesia Ulama Chapter Maros, Regional Tourism Promotion Board Maros (BPPD Maros) obtained through correspondence. Data collection tools are checklists and literature surveys to collect secondary data. The results show that the full availability of halal tourism destination products, including the availability of halal attractions, facilities, accessibility, programs and packages. However, aspects of government support need to increase the support to Bantimurung as a halal tourism destination. Based on the human capital indicator, it is believed that some indicators of human capital that understand tourism need to be increased. In addition, indicators of infrastructure for R&D were sub-optimally provided.